Forsoning og ret Kristelige overvejelser over rettens grundlag - Nissen, Ulrik B. (Dansk Teologisk Tidsskrift, 2009)
The discussion about the identity of Christian ethics continues to be an important issue in a Danish context. This is partly due to the legacy of K. E. Løgstrup. This question is also important in the light of the discussion about the relation between religion and politics. In the present article it is argued that a Lutheran attempt to keep religion and politics separate from each other is both a misreading of Luther and a highly problematic venture in a contemporary society. From an ecclesiological standpoint it is further argued that even if religion and politics are inseparable, this does not entail a relinquishment of the common political discourse. Finally, the article argues – from a Lutheran standpoint – for a possible understanding of the sources of public law as encompassing the unity and difference of religion and politics at one and the same time.